REMOVAL OF METALLIC IMPURITIES FROM QUARTZ SAND USING OXALIC ACID - Suratman Suratman (Puslitbang tekMIRA, 2015)
Quartz sand of Mojosari deposit from Rembang, Central Java has been beneficiated using oxalic acid to en- hance its purity, especially that is associated with the removal of iron oxide impurities. The removal of metallic impurities has been studied under experimental conditions to optimize the process parameters such as oxalate concentration (0.1-0.5M), leaching temperature (25-50°C) and pH of solution (1-5). The optimum leaching pro- cess removed iron from originally 1.44% to reach a level of 0.243% (82% removal of iron) with the SiO2 content increases from 95.50 up to 97.77%. The obtained beneficiated quartz sand matches the required Fe level for glass insulating fibers industry, which is less than 0.3%. The best result was yielded under experimental condi- tion using oxalic acid at concentration of 0.3M, pH 1, temperature of 40°C for 4 hours of leaching process. The experimental results of this study have opened up a practically significant and technically viable approach for the production of quartz sand suitable for glass insulating fiber industry.